Underpricing Dan Faktor - Faktor Yang Mempengaruhi - Sjahruddin '; Yusralaini ' (Jurnal Ekonomi, 2009)
Many research about initial public offering or shortened by IPO conducted to explain the phenomenonIPO which oppose against the theory of market efficiency, which is initial return experiencing ofunderpricing. This article is written to add literature (in) the area by taking object of initial publicoffering research in Jakarta Stock Exchange for the period of 1993 – 1997. this study show thephenomenon underpricing is also happened in Stock Exchange Jakarta. These finding supports thefinding of differ from various world comer.Hereinafter, we form the model by including some factor which theoretically and also empiricalstanding a chance can explain the phenomenon. There are three factors taken that are mount theadvantage, reputation of auditor and reputation of emission guarantor. Result of this study indicatesthat not all of three factors used in model significant statistically. We find that only the factor ofreputation of emission guarantor is related to underpriscing significantly, so also with the factorhereinafter, this study find the factor mount the advantage correlate to underpricing negatively andpositive corresponding auditor reputation but not significant.